Percepción de concentración económica de medios de comunicación en México - Cisneros, Isaac (El Colegio de México, 2020)
What are the characteristics of citizens who perceive a high concentration of media ownership in Mexico? Three explanations are put forward to answer this question. The first emphasizes political motivation, the second people’s levels of sophistication and the third digital cleavage. Using quantitative analysis techniques and data from the Americas Barometer Mexico survey of 2016, the results show that political motivation expressed in opinions in favor of the nationalization of industries and people with greater sophistication consider that in Mexico, the media is controlled by a small number of  economic groups.